A Truth-Based Epistemological Framework for Supporting Teachers in Integrating Indigenous Knowledge into Science Teaching. Issue 3 (1st September 2016) - Zinyeka, Gracious; Onwu, Gilbert O.M.; Braun, Max
Abstract : Integrating indigenous knowledge (IK) into school science teaching is one way of maximising the socio-cultural relevance of science education for enhanced learners' performance. The epistemological differences however between the nature of science (NOS) and nature of indigenous knowledge (NOIK) constitute a major challenge for an inclusive IK-science curriculum integration. This article is about the application of a truth-based epistemological framework designed to support teachers to make decisions on how specific pieces of indigenous knowledge (local traditional practices and technologies) may be included in science lessons. First, an attempt was made to develop a truth-based epistemological framework for identifying epistemology(ies) of indigenous knowledge and practices. Second a group of science teachers used the truth-based epistemological framework to examine ways in which some specified IK practices that comprised a coherent set of knowledge themes on health, agriculture and technology could be integrated into the school science curriculum in a valid and legitimate way. The IK practices used in the study were systematically identified and documented by means of personal observations and interviews of key informants in a rural community in Zimbabwe. The main findings of the study showed that the truth-based epistemological framework was useful in providing an epistemological basis for including some IK practices in science teaching and learning. As a tool for pedagogy the framework enabled the science teachers to reconsider and change their valuing of Indigenous knowledge Systems (IKS), more specifically in ways in which local knowledge can validly be incorporated into school science teaching.